China : Innovations in Agricultural Insurance, Technical Annexes - World Bank (Washington, DC, 2013)
This report explains why agricultural insurance is expensive to deliver to small farm households, details risk assessment in four provinces, and recommends China put more resources in developing products that are more suited to an agricultural economy that is dominated by small farm households. The report discusses the important role of government in supporting the legal and regulatory environment, access to data for new product development, risk sharing, and broader education of all stakeholders about the benefits of agricultural insurance. It also explains why this form of subsidy could provide improved incentives versus a direct subsidy for farmer premium. The report concludes with principle recommendations involving scalable product solutions, risk financing strategy, intuitional capacity building and technical assistance, legal and regulatory framework, and government support and public subsidies.